IMPLEMENTATION OF GOOD MANUFACTURING PRACTICES (GMP) AND SANITATION STANDARD OPERATING PROCEDURES (SSOP) IN THE FREEZING PROCESS OF SCABBARD FISH AT PT. PUTRI INDAH, BELAWAN - Harahap, Kurnia Sada; Saputra, Eko Novi; Muharami, Nurkasih (Politeknik Kelautan dan Perikanan Dumai, 2025)
The implementation of Good Manufacturing Practice (GMP) and Sanitation Standard Operating Procedure (SSOP) is very important to ensure product quality and safety in the food processing industry. In this paper, the implementation of both procedures is discussed during a research at PT Putri Indah Belawan, a company engaged in the freezing of ribbon fish. The main objective of this activity is to implement GMP and SSOP in the freezing process of ribbon fish at PT Putri Indah Belawan. Data collection was carried out through direct observation at every stage of the production process, from receiving raw materials to packaging. The results of the observation showed that most of the GMP and SSOP procedures had been implemented well. However, there were still several areas that still needed improvement, such as stricter cleanliness monitoring and more systematic quality control recording as well as uneven employee training, which was caused by the rotation of new employees every week. Overall, the implementation of GMP and SSOP at PT Putri Indah Belawan was quite good, but need improvement so that product quality could be more optimal.